How Clinical Trial Data Sharing Platforms Can Advance the Study of Biomarkers. Issue 3 (September 2019) - Li, Rebecca; Sim, Ida
Although data sharing platforms host diverse data types the features of these platforms are well-suited to facilitating biomarker research. Given the current state of biomarker discovery, an innovative paradigm to accelerate biomarker discovery is to utilize platforms such as Vivli to leverage researchers' abilities to integrate certain classes of biomarkers.